THE ROLE OF EMPLOYEE ENGAGEMENT AND JOB SATISFACTION IN THE EFFECT OF REWARDS AND RECOGNITION ON INTENTION TO STAY - Fajrin, Andini; Taufik, Edi Rahmat; Kambara, Roni (Yayasan Education and Social Center, 2025)
The high employee turnover in the manufacturing sector, especially at PT IHI Power Service Indonesia (15% per year), is a strategic challenge for organizational effectiveness and efficiency. This study aims to analyze the effect of Reward and Recognition on Intention to Stay, by considering the mediating role of Employee Engagement and Job Satisfaction. A quantitative approach was used with a survey method on 182 permanent employees. The research instrument was a Likert-scale closed questionnaire, which was analyzed using PLS-SEM. The results showed that Reward and Recognition positively and significantly affect Intention to Stay directly and indirectly through Employee Engagement and Job Satisfaction. The chain mediation model shows that reward and recognition increase employee engagement, increase job satisfaction, and strengthen the intention to stay. The practical implication is that companies must implement a fair and relevant reward system and integrate it with strategies to increase engagement and job satisfaction and reduce employee turnover intention. Theoretically, this study enriches the HRM literature through a dual mediation model based on Social Exchange Theory in the context of the manufacturing industry in Indonesia.